Soil erosion and global warming in India - LAL, RATTAN (Journal of Soil and Water Conservation, 2020)
Accelerated soil erosion, the rate in excess of the tolerable level of soil loss, constitutes serious environmental and agronomic risks in India. However, the available estimates of land area affected by erosion are highly variable and technique-dependent. Some estimates indicate the land area affected by soil erosion at 30.0 to 32.8 million hectare (Mha) by water erosion and 8.9 to 10.8 Mha by wind erosion. An additional land area affected by vegetation degradation by water erosion is estimated at ~40 Mha. The magnitude of gross soil erosion by water is estimated at 5.1Â±0.4 Gt (15.6 t/ha) per year, of which 34.1Â±1.2% is deposited in the reservoirs. Relative contribution to sediments is 81% from rivers in the north and 19% from those in the south. Risks of soil degradation may be exacerbated with the projected climate change because of the increase in frequency and intensity of extreme events: the drought-flood syndrome. Soil erosion has on-site and off-site effects. On-site, erosion truncates the surface soil, depletes soil organic matter reserves and nutrient contents, reduces plant-available water retention capacity, decreases use efficiency of inputs and reduces agronomic productivity. Off-site, soil erosion aggravates non-point source pollution, exacerbates risks of toxic algal blooms and eutrophication, and increases emission of greenhouse gases into the atmosphere. Site-specific data, based on watershed-based longterm research, are needed to understand the fate of erosion-induced transport of soil carbon.